Investigation of optical spectra of dielectric crystals - Koketay, T.A.; Tussupbekova, A.K.; Mussenova, E.K. (Institute of Physics Publishing, 2018)
Optical spectra of crystals oxyhalides of bismuth are investigated in this work. When measuring the transmission spectra of single crystals of oxyhalides of bismuth in the direction perpendicular to the layers, a large number of peaks associated with the occurrence of the interference pattern when light is reflected from the layers. The intense absorption band at 4.0 eV for BiOCl crystal has a doublet structure, in the case of the BiOBr crystal splitting is less pronounced. Upon excitation in the fundamental absorption region there photoluminescence spectra are investigated. The spectrum of luminescence of BiOCl crystal is not elementary and it consists of two bands of radiation. The presence in the excitation spectra and luminescence shortwave bands strongly depends on the degree of purity of the bismuth oxide is used in the synthesis oxyhalides of bismuth crystal. Thus, it allows to link the short-wave emission band with uncontrolled impurity, and long-wave – with its own glow crystal substrate.